Pengaruh Kualitas Pelayanan terhadap Kepuasan Publik di Badan Pengelolaan Pajak dan Retribusi Daerah Kota Palembang - Wahyuli, Yofitri Heny (Jurnal Analisis Sosial Politik, 2021)
This research is correlational research. With the correlation technique can be known relationship variation in a variable with other variations, the magnitude or height of the relationship is expressed in the form of correlation coefficient. Based on this opinion, the authors conducted a correlational study to determine the effect of service quality on public satisfaction in the Regional Tax Management and Retribution Palembang City. The results of research and discussion explain the reliability, responsiveness, assurance, empathy and direct evidence affect the Public Satisfaction at the Regional Tax and Retribution Agency Palembang City. This explains the public (the people) are satisfied with the performance of the services of the Palembang City Municipal Tax and Retribution Agency related to the reliability, responsiveness, assurance, empathy and direct evidence. Reliability, responsiveness, assurance, empathy and direct evidence also give effect to Public Satisfaction at Local Tax and Retribution Agency of Palembang City. This explains precisely the preparation and embodiment of service variables consisting of reliability, responsiveness, assurance, empathy and direct evidence in the operations of the Regional Tax and Retribution Agency of Palembang City, especially in forming Public Satisfaction requesting services. Correlation can also be seen that the level of correlation between variables of service quality variables such as reliability, responsiveness, assurance, empathy and direct evidence, in a correlation position is very weak and even considered none at all. Unless the correlation between responsiveness and empathy is in very strong position.